Application of modern technologies in education of medical students in the subject of medical biology - Prikhodko, O. B.; Popovуch, A. P.; Aliyeva, O. G.; Maleyeva, G. Yu.; Havrylenko, K. V.; Shemetenko, O. O.; Приходько, Олександр Борисович; Попович, Аліса Петрівна; Алієва, Олена Геннадіївна; Малєєва, Ганна Юріївна; Гавриленко, Ксенія В'ячеславівна; Шеметенко, Олександра Олександрівна (My University, 2023)
Introduction. The main trend of the modern educational space is the innovative development of society and the education of a person who is able to generate ideas, look for alternative solutions to standard and problematic situations. Therefore, one of the strategic tasks of higher medical education in Ukraine is the introduction of innovative pedagogical technologies, which are based on the development of new content, methods and teaching tools. [1, 2, 3].